Keunggulan Komperatif Metode Weighted Product (WP) Dalam Pemilihan Karyawan Terbaik Berbasis Web (Studi Kasus: Naw Shop) - Muhammad Muslih Anwar; Ferry Agus Sianipar (CV. Multi Kreasi Media, 2022)
The development of information technology, especially the Internet, is a driving factor for the development of e-commerce. The Internet is a global network that unites computer networks around the world, thus enabling communication and interaction between one another throughout the world. Naw Shop is one of the businesses in the field of online sales that sells various kinds of baby needs. In order to maintain and improve the quality of employees, employers need to conduct an employee performance appraisal in the form of selecting the best employees. Selection of the best employees is an important aspect in performance management. The purpose of this research is to create a decision support system to assist leaders in making decisions to select the best employees according to the criteria that have been determined at the Naw Shop. And at the same time the comparison of the Simple Additive Weighting (SAW) method with the Weighted Product (WP) method in determining the selection of the best employees at the Naw Shop. The results of this study are by implementing a Decision Support System in finding the best employees at Naw Shop with an easyto-understand display system so that it can make it easier for leaders to evaluate employees and find out the results quickly.